INTERPERSONAL COMMUNICATION STRATEGIES OF MILITARY PARENTS IN ENCOURAGING OPENNESS IN THEIR CHILDREN - Haryana, Doni Prasetyo Tri Sumara; Sunarto; Nilamsari, Natalina (Universitas prof. Dr. Moestopo (Beragama), 2025)
Interpersonal communication strategies between parents and children play a crucial role in fostering openness, especially in military families characterized by strict discipline and hierarchy. This study analyzes the communication patterns applied by military parents in supporting children's openness and identifying barriers in family communication within the military dormitory environment. Using a qualitative phenomenological approach, this study examines parent-child communication experiences through observation, in-depth interviews, and documentation. Specifically, Interpersonal Deception Theory (IDT) is used to understand how parents adjust openness in communication to avoid conflict or maintain family stability. The findings indicate that communication in military families relies on instructive, experience-based, and adaptive strategies, as well as the use of symbols and codes. However, overly formal and authoritative patterns can limit children's ability to express emotions and opinions. Parents often filter or simplify information about military duties and family issues, potentially reducing children's openness. Additionally, the hierarchical structure influences trust and emotional closeness. The study suggests that balancing authority with emotional support is essential to fostering healthy communication and ensuring a more open and supportive family environment.